2021
DOI: 10.3390/f12040414
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Forest Storms—Taking Stock of After-Vaia Situation of Local Roundwood Markets in Northeastern Italy

Abstract: Large timber availability after storms can lead to a drop in timber prices that can impact local markets. The Vaia storm, which occurred in Northeastern Italy at the end of October 2018, felled large volumes of timber, particularly spruce. To estimate the loss in volume and value connected to Vaia, data of roundwood sales from four local markets (Province of Trento, Province of Bolzano, Veneto Region and Friuli Venezia Giulia Region) were collected before and after Vaia, as well as reports on the status of sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…The study area coincides with the Italian area hits by the VAIA windstorm as reported by Chirici et al (2018) [47] in the following Regions of Italy: Trentino Alto Adige, Veneto, Friuli Venezia Giulia, Lombardia, Piemonte, and Valle d'Aosta (Figure 1), for a total of 67,000 km 2 covered by forest for 144,651.1 ha following the FAO forest definition [48,49]. The VAIA storm hit the area in the night between 28 and 29 October 2018 with winds up to 200 km/h [45].…”
Section: Study Area and Vaia Windstormsupporting
confidence: 71%
See 1 more Smart Citation
“…The study area coincides with the Italian area hits by the VAIA windstorm as reported by Chirici et al (2018) [47] in the following Regions of Italy: Trentino Alto Adige, Veneto, Friuli Venezia Giulia, Lombardia, Piemonte, and Valle d'Aosta (Figure 1), for a total of 67,000 km 2 covered by forest for 144,651.1 ha following the FAO forest definition [48,49]. The VAIA storm hit the area in the night between 28 and 29 October 2018 with winds up to 200 km/h [45].…”
Section: Study Area and Vaia Windstormsupporting
confidence: 71%
“…), and Pinus (Pinus spp. ), however some damages were reported also in broadleaves forests such as in beech stands (Fagus sylvatica L.) [48]. Preliminary field recognition and manual photointerpretation of satellite data showed that a total of 42.525 ha of forests were damaged by the storm [47,49].…”
Section: Study Area and Vaia Windstormmentioning
confidence: 99%
“…The Vaia storm, which occurred in Northeastern Italy at the end of October 2018, felled large volumes of timber causing serious ecological and financial losses, with unexpected challenges for forest managers. The wind gusts exceeded 200 km h −1 ; over 490 Municipalities in six administrative Regions registered forest damages over an area of 67,000 km 2 [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the aforementioned issues, the post-windthrow management should provide for rapid and efficient salvage logging operations, in order to quickly remove timber from damaged stands and limit the economic loss [7]. Salvage logging implementation is still a matter of debate, since it was reported that it may cause negative impacts on forest communities [8].…”
Section: Introductionmentioning
confidence: 99%